Kesan perubahan dasar kewangan ke atas perkembangan sektor hartanah - Salleh, Dani (2000)
The objective of this paper is to discuss the impacts to government financial policy on property sector development. This paper also gives some emphasis on the efforts of the government to ensure the availability of adequate financing at reasonable rates to enable the private sector housing programmes to be achieved.